Desenvolvimento de mudas de tamarindeiro: tamanhos de recipiente, substratos, peso de sementes e profundidades de semeadura - Almeida, Marcelo Sales de (2008)
This study expanded the knowledge on tamarind (Tamarindus indica L.) seedling production by analyzing the effects of different container sizes and vermiculite doses in a commercial substrate and seed size and different sowing depths in a nursery seedling production. The experiments were done at the experimental farm Água Limpa in the sector of Fruit Crops, in a nursery with anti-aphid screens, with 0.38 mm2 opening. The farm is located at 19º05 23 S and 48º21 28 W, at 792 m altitude, in the county of Uberlândia, Minas Gerais, Brazil. The experimental design of the trials were randomized blocks, in a 3 x 3 or 2 x 3 factorial. In the first trial, were utilizadas three vermiculite doses (0%, 10% or 20% v v-¹) in three container sizes (18 x 30 cm, 20 x 25 cm or 25 x 35 cm), and in the second trial, utilizou-se two seed sizes (small and large) and three sowing depths (1cm; 2cm or 3cm), both of them with 5 repetitions and 5 plants per plot. The experiments were done from December 26 2006 to June 4 2007. In the first trial, results indicated that tamarind seedlings were not affected by container size, nor by the use of vermiculite. However, the largest container (25 x 35 cm) yielded longer root length, although reducing stem diameter and above ground fresh and dry matter. Mixing vermiculite to the substrate yielded better results for stem diameter, number of leaves, fresh and dry matter of roots and above ground mass. In the second trial, the results indicated that bigger seeds yielded greater quality tamarind seedlings for plant height, stem diameter, fresh and dry matter for above ground mass and roots. There were no significant differences in the parameters evaluated as a function of sowing depth. CHAPTER I: This study evaluated the effects of different vermiculite doses and container sizes in the development and quality of tamarind seedlings. The experiment was done in a nursery with anti-aphid screens, with 0.38 mm2 opening, in the sector of fruit Experimental Farm Água Limpa, county of Uberlândia (MG), from December 26 2006 to June 4 2007. The experimental design was randomized blocks , in a 3 x 3 factorial, with 5 repetitions and 5 plants per plot. The factors were three vermiculite doses (0%, 10% or 20% v v-¹) and three container sizes (18 x 30 cm, 20 x 25 cm or 25 x 35 cm). The development of tamarind seedlings was evaluated by the determination of the number of leaves, stem diameter, plant height, root length, fresh and dry weight of roots and above ground matter. The results showed that tamarind seedling height was not affected by container sized nor by the use of vermiculite. The largest container (25 x 35 cm) yielded better root length; however, stem diameter and above ground fresh and dry matter were reduced. Mixing vermiculite to the substrate yielded better results for stem diameter, number of leaves, fresh and dry matter of roots and above ground mass. CHAPTER II: The effect of seed size and different sowing depths on tamarind (Tamarindus indica L.) seedling vigor and vegetative growth was evaluated in a trial done in a screened nursery, with 0.38 mm2 opening, at the experimental farm Água Limpa, in a nursery with anti-aphid screens, in the county of Uberlândia,. The farm is located at 18º55 33 S and 48º17 19 W, at 872 m altitude, Minas Gerais, from December 26 2006 to June 4 2007. The experimental design was randomized blocks, in a 2 x 3 factorial, with 5 repetitions and 5 plants per plot. The factors were two seed sizes, small and large (65.60 g and 94.54 g respectively), defined according to the weight of 100 seeds and three sowing depths (1cm; 2cm or 3cm). The number of leaves, stem diameter, plant height, root length, fresh and dry weight of roots and above ground matter were evaluated. The results indicate that tamarind seed size affected seedling initial development. There were no significant differences in the parameters evaluated as a function of sowing depth.